EXCITED-STATE TWO-PROTON TAUTOMERISM IN HYDROGEN-BONDED N-HETEROCYCLIC BASE PAIRS - Taylor, Carl Al (1969)
The optical absorption and luminescence spectra of 7-azaindole and its doubly hydrogen-bonded dimer were investigated as a model for the study of electronic interactions in DNA base pairs. It is demonstrated that a biprotonic phototautomerism occurs in the dimer and in suitable ethanol solvates in fluid solvents but that the phenomenon is not observed in a rigid solvent matrix. The normal violet structured fluorescence of 7-azaindole monomer becomes a broad green fluorescence in the tautomer. It is shown that spectral band interchanges, excimer formation, excited-state single-proton transfer, and proton tunneling cannot account for the luminescence change, but that the molecular exciton effect facilitates the cooperative two-proton reversible transfer. It is proposed that biprotonic phototautomerism with molecular environmental sensitivity could provide a mechanism for the initial step in ultraviolet mutagenic effects in DNA.